Correction: Functional Analysis of the Na+,K+/H+ Antiporter PeNHX3 from the Tree Halophyte Populus euphratica in Yeast by Model-Guided Mutagenesis. - PLOS ONE Staff (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0104147.].